Physical activity and nutrition education at the school environment aimed at preventing childhood obesity: evidence from systematic reviews - Paulo Henrique Guerra; Jonas Augusto Cardoso da Silveira; Emanuel Péricles Salvador (Elsevier, 2016)
ABSTRACT OBJECTIVE: To organize the main findings and list the most frequent recommendations from systematic reviews of interventions developed at the school environment aimed at reducing overweight in children and adolescents. DATA SOURCE: Searches for systematic reviews available until December 31, 2014 were conducted in five electronic databases: Cochrane, PubMed, SciELO, SPORTDiscus, and Web of Science. Manual search for cross-references were also performed. SUMMARY OF THE FINDINGS: Of the initial 2139 references, 33 systematic reviews adequately met the inclusion criteria and were included in the descriptive summary. In this set, interventions with periods of time greater than six months in duration (nine reviews), and parental involvement in the content and/or planned actions (six reviews) were identified as the most frequent and effective recommendations. Additionally, it was observed that boys respond more effectively to structural interventions, whereas girls respond to behavioral interventions. None of the included reviews was able to make inferences about the theoretical basis used in interventions as, apparently, those in charge of the interventions disregarded this component in their preparation. CONCLUSIONS: Although the summary identified evidence with important applications in terms of public health, there are still gaps to be filled in this field of knowledge, such as the effectiveness of different theoretical models, the identification of the best strategies in relation to gender and age of participants and, finally, the identification of moderating variables to maximize the benefits provided by the interventions.